PENGARUH BUDAYA ORGANISASI DAN KOMITMEN TERHADAP KINERJA GURU PADA SMK GKPS 2 PEMATANGSIANTAR - Sofi Chrisdayanti Purba; Darwin Lie; Efendi Efendi; Andy Wijaya (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2018)
The formulation of this research problem is how the influence of Cultural Organization and Commitment to the Teacher Performance at SMK GKPS 2 Pematangsiantar. The research method used in this paper is literature research and field research. Its population is employees of SMK GKPS 2 Pematangsiantar amounted to 64 people. The data used are data by qualitative and qualitative data, and data collection techniques by questionnaire, interview and documentation. Then the technique of data analysis using qualitative descriptive method and quantitative descriptive method. Results of analysis of multiple linear regression is Ŷ = 68,710 + 0,715X1 + 0,914X2 means there is a positive influence between cultural organization and commitment on teacher performance. The strength of the relationship between the three variables is strong, is r = 0,672. From the coefficient of determination can be explained high low employee performance 45,2% and the remaining 54,8% explained by other factors that are not discussed in this study. From the results of processing and calculation of the questionnaire, the authors get the conclusion that the cultural organization and commitment applied SMK GKPS 2 Pematangsiantar have a positive and significant effect on teacher performance. This is proven by hypothesis testing simultaneously, where the test result fhitung (25,170) > fhitung (3,15) with significance level 0,000 < alpha 0,05. Keywords: Cultural Organization, Commitment and Teacher Performance